Utility-scale photovoltaic generators: A review on trends, grid code requirements and challenges - Tan N.M.L.; Ramasamy A.K.; Ramachandaramurthy V.K.; Marsadek M.; Othman M.R.; Ariffin I. (Institute of Advanced Engineering and Science, 2023)
This paper provides an overview of the global trends in utility-scale photovoltaic (PV) installed capacity. This paper also presents a comparison of grid-connection requirements of six countries in the continents of Europe, Asia, Africa, and Australia for utility-scale PV generators in normal and abnormal grid conditions. Many country-based grid codes and international standards (IEEE 1547) for interconnection of inverter-based renewable energy generators are demanding stricter grid-connection compliance from utility-scale PV generators to ensure power system safety and reliability as its penetration level increases. This paper then discusses the economic and technical impacts, and explores the preparedness of PV generation systems in meeting the grid code requirements. Copyright 2020 Institute of Advanced Engineering and Science. All rights reserved.